A new species of gall midge (Diptera: Cecidomyiidae) attacking jujube, Ziziphus jujuba in China - Jiao, Ke-Long; Han, Pei-Jin; Yang, Ming-Lu; Xiong, Ren-Ci; Wang, Yuan-Hong; Bu, Wen-Jun (Zootaxa, 2017)
Dasineura jujubifolia Jiao & Bu, sp. nov., a gall midge feeding on jujube, Ziziphus jujuba Miller (Rhamnaceae), a fruit tree cultivated extensively in large areas of China, is described and illustrated based on specimens collected from Alar (Xinjiang, China). The new gall midge species causes rolled leaf galls on Ziziphus jujuba in Northwestern China. Brief notes on the biology of the jujube gall midge are given.